2021
DOI: 10.3748/wjg.v27.i27.4276
|View full text |Cite
|
Sign up to set email alerts
|

Viral infections in inflammatory bowel disease: Tips and tricks for correct management

Abstract: Over the past decades, the treatment of inflammatory bowel diseases (IBD) has become more targeted, anticipating the use of immune-modifying therapies at an earlier stage. This top-down approach has been correlated with favorable short and long-term outcomes, but it has also brought with it concerns regarding potential infectious complications. This large IBD population treated with immune-modifying therapies, especially if combined, has an increased risk of severe infections, including opportunistic infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 194 publications
0
22
0
Order By: Relevance
“…Hepatitis C prevalence in IBD is similar to the general population[ 168 ]. The risk of HCV reactivation under immunosuppressive therapies used in IBD is low[ 172 , 173 ]. Small case series reported successful treatment of hepatitis C with direct-acting antiviral (DAA) in patients on anti-TNF therapy[ 170 ] and no drug-drug interaction between DAA and anti-TNF has emerged[ 174 ]; thus, concomitant treatment with DAA and anti-TNF seems to be safe, although more studies specifically addressing this setting are needed.…”
Section: Ibd and Viral Hepatitis B And Cmentioning
confidence: 99%
“…Hepatitis C prevalence in IBD is similar to the general population[ 168 ]. The risk of HCV reactivation under immunosuppressive therapies used in IBD is low[ 172 , 173 ]. Small case series reported successful treatment of hepatitis C with direct-acting antiviral (DAA) in patients on anti-TNF therapy[ 170 ] and no drug-drug interaction between DAA and anti-TNF has emerged[ 174 ]; thus, concomitant treatment with DAA and anti-TNF seems to be safe, although more studies specifically addressing this setting are needed.…”
Section: Ibd and Viral Hepatitis B And Cmentioning
confidence: 99%
“…Other AIDS-related illnesses, such as respiratory opportunistic infections, may coexist with COVID-19, which might make diagnosis, clinical course, patient care, and morbidity and mortality more di cult or fatal [5]. Patients are impacted by COVID-19, especially when there is severe immunosuppression brought on by AIDS and when HIV-related opportunistic infections are present [6].…”
Section: Discussionmentioning
confidence: 99%
“…9 Inflammatory bowel disease (IBD) is associated with cellular and humoral immune dysfunctions, resulting in susceptibility to viral infection and reactivation; studies in Western countries and Japan have demonstrated that patients with IBD are at an increased risk for herpes zoster. [9][10][11][12][13] The use of corticosteroids, thiopurines, TNFi, and combination therapy have been reported to increase the risk of herpes zoster. 11,12,14 However, the association between herpes zoster and UC therapies in patients with UC in Japan is uncertain due to a lack of data from Asian patients with UC.…”
Section: Introductionmentioning
confidence: 99%
“…Herpes zoster, caused by the reactivation of latent varicella zoster virus, is a major public health issue and the incidence rate of herpes zoster in Japan has been previously estimated to be 0.49 per 100 patient-years (95% confidence interval [CI], 0.49–0.50) in the general population [ 9 ]. Inflammatory bowel disease (IBD) is associated with cellular and humoral immune dysfunctions, resulting in susceptibility to viral infection and reactivation; studies in Western countries and Japan have demonstrated that patients with IBD are at an increased risk for herpes zoster [ 9 - 13 ]. The use of corticosteroids, thiopurines, TNFi, and combination therapy have been reported to increase the risk of herpes zoster [ 11 , 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%